FAMILIAL ORAL LICHEN PLANUS - A REVIEW OF THE LITERATURE AND A CASE SERIES REPORT - Carmen Larisa Nicolae; Elena Claudia Coculescu; Mihaela Tanase; George Ion; Bogdan-Ioan Coculescu (Romanian Society of Oral Rehabilitation, 2024)
Background: Lichen planus (LP) is a complex condition with numerous and polymorphic clinical manifestations. Although oral lichen planus (OLP) usually appears as isolated cases in the population, there have been reports of this condition manifesting among members of the same family. Therefore, genetic factors represent a potential etiologic factor, as demonstrated in several studies. Aim of the study: To present the clinical-evolutionary characteristics and treatment response in a series of 8 different cases of OLP from 4 different families. Results: All patients included in the study were women, with a mean age of 44.87 years, non-smokers, and had associated general conditions such as psoriasis, autoimmune thyroiditis, or hepatitis C. The most common clinical form was the atrophic-keratotic type, involving 2-3 topographical areas, and the majority of patients reported painful symptoms. In half of the patients, we observed a good progression and significant remission. Discussion: A possible factor associated with the pathogenesis of OLP is genetics. Familial LP appears at younger ages and can manifest with widespread lesions. The study of familial OLP cases reveals certain clinical-evolutionary characteristics, which are sometimes atypical. Conclusion: Studying familial OLP cases is necessary to better understand the specific manifestation patterns and to assess treatment response. Additionally, these cases may have a higher potential for malignant transformation.